2020
DOI: 10.1021/acsomega.0c01483
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Reaction Mechanisms of Furfural Hydrodeoxygenation on a CuNiCu(111) Bimetallic Catalyst Surface from Computation

Abstract: In this study, the selectively catalytic hydrodeoxygenation of furfural (F–CHO) to 2-methylfuran (F–CH 3 ) on the CuNiCu(111) bimetallic catalyst surface was systematically investigated based on the periodic density functional theory, including dispersion correction. The formation of furfuryl alcohol (F–CH 2 OH) involved two steps: the preferred first step was the hydrogenation of the branched C atom, forming the alkoxyl intermediate (F–CHO + H = F–CH 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…14 Over the past few decades, liquid phase hydrogenation of FF to FA with various metal-based heterogeneous catalysts has been extensively studied experimentally and theoretically. [14][15][16][17][18][19][20][21][22][23][24][25][26] In this liquid-phase process, in which molecular hydrogen (H 2 ) was used as the hydrogen source, solvent and high H 2 pressures are required. Compared to the H 2 -hydrogenation reaction, catalytic transfer hydrogenation (CTH) using renewable and liquid-phase hydrogen sources, such as alcohols, formic acid, formate and hydrosilane, represents an attractive, safer and more convenient alternative for the hydrogenation of aldehydes and ketones into alcohols.…”
Section: Introductionmentioning
confidence: 99%
“…14 Over the past few decades, liquid phase hydrogenation of FF to FA with various metal-based heterogeneous catalysts has been extensively studied experimentally and theoretically. [14][15][16][17][18][19][20][21][22][23][24][25][26] In this liquid-phase process, in which molecular hydrogen (H 2 ) was used as the hydrogen source, solvent and high H 2 pressures are required. Compared to the H 2 -hydrogenation reaction, catalytic transfer hydrogenation (CTH) using renewable and liquid-phase hydrogen sources, such as alcohols, formic acid, formate and hydrosilane, represents an attractive, safer and more convenient alternative for the hydrogenation of aldehydes and ketones into alcohols.…”
Section: Introductionmentioning
confidence: 99%
“…Although the electrochemical hydrogenation of furfural (ECHFF) has been experimentally studied to improve the selectivity of target products and energy conversion efficiency, the theoretical research on the ECHFF process needs to be clarified. There are very few studies about theoretical research on ECHFF. Shan et al reported the mechanistic study of the electrocatalytic hydrogenation of FF on Ag, Pb, and Ni.…”
Section: Introductionmentioning
confidence: 99%
“…adsorption of methanol as compared to that of other small molecules such as H 2 O, CO 2 , CH 4 , C 2 H 2 , C 2 H 4 , C 2 H 6 , etc. 52 This very strong dissociative adsorption of CH 3 OH indicates the rather low stability of the (001) surface. It is expected that the metallic Mo 2 C(001) surface can be easily oxidized or carburized.…”
Section: Introductionmentioning
confidence: 99%
“…It is expected that the metallic Mo 2 C(001) surface can be easily oxidized or carburized. 52 Nevertheless, the CO formation was computed for comparison, and it was found that the energy barrier is 2.81 eV. To complete the reaction, the desorption of CO and H 2 was computed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation